Evaluation of Antimicrobial Opinions and Uses in Small and Large Animal Veterinary Practice in Washington State - Rott, Elizabeth Grace (My University, 2023)
Antimicrobial resistance in bacteria has been a prominent topic of concern for the public health sector in the 21st century. While there are many factors that contribute to increasing AMR in the human population, antimicrobial use in companion animal and large animal veterinary practices is of particular interest due to the One Health paradigm. Understanding antimicrobial prescription habits in veterinary medicine can help to characterize the impacts of regulations and other interventions currently used in veterinary medicine to reduce unnecessary antimicrobial prescription and the potential development of resistant pathogens. A survey was designed and made available to Washington State practicing veterinarians during the time period of February 8, 2023 to March 31, 2023. The survey consisted of three sections designed to evaluate antibiotic prescription tendencies and general opinions regarding antimicrobial stewardship in veterinary medicine. Hypothetical clinical scenarios were created to inquire about antibiotic usage in common clinical situations in small, mixed, and large animal veterinary practice in Washington state. In total, 54 veterinarians completed the survey including 46 small animal veterinarians, 17 mixed animal vets, and 15 large animal vets. We evaluated correctness of antibiotic usage judgments for the scenario-based questions. Results showed an approximately 62% correct response rate for small animal veterinarians and an approximately 32% correct response rate for mixed animal veterinarians, and approximately 45% correct response rate for large animal veterinarians. When asked which factors in veterinary medicine may contribute or play a role in an antimicrobial resistance, 85% selected owner/producer compliance, 78% selected veterinary medicine prescription practices, 78% selected prescription of broad-spectrum antimicrobial drugs for treatment, and 50% selected lack of veterinary education on antimicrobial use and stewardship. Finally, a majority of participants (70%) agreed that client finances influence the manner they prescribe antimicrobials, and a majority of participants stated that client expectations of receiving antimicrobials does not influence the manner in which they prescribe. These findings emphasize the importance of continued efforts to promote responsible use of AMDs in veterinary medicine practice, including improved training through continuing education opportunities, intuitive stewardship, resources, and the implementation of guidelines and regulations to ensure that AMDs are used judiciously.
Thesis (Master's)--University of Washington, 2023
Keywords: Toxicology; Environmental health